2005
DOI: 10.1007/s00262-005-0094-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the γδ T cell response to acute leukemia

Abstract: gammadelta T cells exhibit an in vitro response to primary leukemia blasts that is manifested by proliferation, an increased proportion of Vdelta1+ T cells, and cytotoxicity to the primary leukemia blasts. The Vdelta1+ T cell population is also predominant in newly diagnosed leukemia patients likely due to a loss of circulating Vdelta2+ T cells. A small proportion of newly diagnosed patients showed Vdelta1 CDR3 region similarity. These findings suggest a role for gammadelta T cells in the immune response to le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 34 publications
6
33
0
Order By: Relevance
“…Shen et al (16) also showed similar results and they postulated that the presence of TCR Vd clonality in a few T cells is a normal phenomenon and a result of non-specific random proliferation. A previous work showed TCR Vd 1 was preferably expressed in the hu man intestinal epithelial cells, and its expression was also frequently found in autoimmune diseases, tu mors and bronchial asthma (18). Our results re vealed the TCR Vd 6 T cells had an increased trend toward oligoclonal proliferation following SIT.…”
Section: Discussionsupporting
confidence: 73%
“…Shen et al (16) also showed similar results and they postulated that the presence of TCR Vd clonality in a few T cells is a normal phenomenon and a result of non-specific random proliferation. A previous work showed TCR Vd 1 was preferably expressed in the hu man intestinal epithelial cells, and its expression was also frequently found in autoimmune diseases, tu mors and bronchial asthma (18). Our results re vealed the TCR Vd 6 T cells had an increased trend toward oligoclonal proliferation following SIT.…”
Section: Discussionsupporting
confidence: 73%
“…Although the biological implications of this finding are incompletely understood, previous studies suggest both a depletion of the Vd2 subset and activation and expansion of the Vd1 subset may be responsible for this. [49][50][51][52][53][54][55][56][57] Whether these findings are unique to T cell-depleted grafts is not clear because there are very few publications on immune reconstitution post HSCT that report on recovery of the gd T cell subpopulation. In general, studies on immune reconstitution post HSCT demonstrate no significant qualitative differences between recipients of T cell-depleted and recipients of unmodified grafts, although immune reconstitution is relatively delayed in the T celldepleted group.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The anti-leukemic role of gd T cells was suggested by a correlation between Vd1 T cells expansion and prognosis following AHSCT. 7,8 Aside from Vd1 T cells, Vg9Vd2 T cells, the main circulating subset, account for 1-10% of human T lymphocytes. Their T cell receptors (TCR) sense non-peptidic-phosphorylated phosphoAntigens (pAgs), such as isopentenyl diphosphate (IPP), an intermediary metabolite of the human mevalonate pathway.…”
Section: Introductionmentioning
confidence: 99%